Some Observations on the Fine Structure of the Giant Nerve Fibers of the Earthworm, Eisenia foetida - Hama, Kiyoshi (The Rockefeller University Press, 1959)
Sectioned dorsal giant fibers of the earthworm Eisenia foetida have been studied with the electron microscope. The giant axon is surrounded by a Schwannian sheath in which the lamellae are arranged spirally. They can be traced from the outer surface of the Schwann cell to the axon-Schwann membranes. Irregularities in the spiral arrangement are frequently observed. Desmosome-like attachment areas occur on the giant fiber nerve sheath. These structures appear to be arranged bilaterally in columns which are oriented slightly obliquely to the long axis of the giant fiber and aligned linearly from the axon to the periphery of the sheath. At these sites they bind together apposing portions of Schwann cell membrane comprising the sheath. Longitudinal or oblique sections of the nerve sheath attachment areas are reminiscent of the Schmidt-Lantermann clefts of vertebrate peripheral nerve. Septa of the giant fibers have been examined. They are symmetrical or non-polarized and consist of the two plasma membranes of adjacent nerve units. Characteristic vesicular and tubular structures are associated with both cytoplasmic surfaces of these septa.